2020
DOI: 10.1111/jocd.13347
|View full text |Cite
|
Sign up to set email alerts
|

Oily sensitive skin: A review of management options

Abstract: Background Due to the ever‐increasing demands for the personalized care, people seek for the tailored management according to the accurate identification of their skin type. The Baumann Skin Type Indicator, which was proposed by Leslie Baumann, is composed of four parameters: oily or dry, resistant or sensitive, pigmented or nonpigmented, and wrinkled or tight. Among these, oily sensitive skin experiences significant discomfort and resists ordinary treatment. Aims In this article, we will review the clinical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…Experts recommend the use of moisturizers to prevent ASRs. 4,11,[21][22][23][24][25][26][27] However, it should be noted that the use of moisturizers on inflamed skin may be poorly tolerated and trigger flare-ups that need to be treated. 22 In this study, the most common preventive or counteractive method was applying a moisturizer.…”
Section: Discussionmentioning
confidence: 99%
“…Experts recommend the use of moisturizers to prevent ASRs. 4,11,[21][22][23][24][25][26][27] However, it should be noted that the use of moisturizers on inflamed skin may be poorly tolerated and trigger flare-ups that need to be treated. 22 In this study, the most common preventive or counteractive method was applying a moisturizer.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the effects on skin barrier, there was a study demonstrated that the TEWL in oily skin people was slightly higher than that of normal skin people 22 . Some people with oily skin also had sensitive skin 23 . Since there are the alteration and imbalance in lipid composition of sebum on the skin.…”
Section: Discussionmentioning
confidence: 99%
“…The average rate of sebum production in normal human skin is about 1 mg/10 cm 2 every 3 h ( Hong et al, 2020 ). If the sebum secretion of human skin exceeds 1.5 mg/10 cm 2 every 3 h, caused by high secretion of the sebaceous glands, then the skin becomes oily.…”
Section: Skin Lipid Conditioningmentioning
confidence: 99%
“…Excessive oil secretion may affect the microbial environment of the face, leading to acne ( Youn, 2010 ). In addition, this can lead to enlarged facial pores and a greasy facial appearance ( Hong et al, 2020 ). Therefore, it is particularly important to clean the face.…”
Section: Skin Lipid Conditioningmentioning
confidence: 99%